Direct pyrolysis and ultrasound assisted preparation of N, S co-doped graphene/Fe3C nanocomposite as an efficient electrocatalyst for oxygen reduction and oxygen evolution reactions - Rani, Karuppasamy Kohila; Karuppiah, Chelladurai; Wang, Sea-Fue; Alaswad, Saleh O.; Sireesha, Pedaballi; Devasenathipathy, Rajkumar; Rajan, Jose; Yang, Chun-Chen (Elsevier Ltd, 2020)
Bifunctional electrocatalysts to enable efficient oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are essential for fabricating high performance metal–air batteries and fuel cells. Here, a defect rich nitrogen and sulfur co-doped graphene/iron carbide (NS-GR/Fe3C) nanocomposite as an electrocatalyst for ORR and OER is demonstrated. An ink of NS-GR/Fe3C is developed by homogeneously dispersing the catalyst in a Nafion containing solvent mixture using an ultrasonication bath (Model-DC150H; power − 150 W; frequency − 40 kHz). The ultrasonically prepared ink is used for preparing the electrode for electrochemical studies. In the case of ORR, the positive half-wave potential displayed by NS-GR/Fe3C is 0.859 V (vs. RHE) and for the OER, onset potential is 1.489 V (vs. RHE) with enhanced current density. The optimized NS–GR/Fe3C electrode exhibited excellent ORR/OER bifunctional activities, high methanol tolerance and excellent long-term cycling stability in an alkaline medium. The observed onset potential for NS–GR/Fe3C electrocatalyst is comparable with the commercial noble metal catalyst, thereby revealing one of the best low-cost alternative air–cathode catalysts for the energy conversion and storage application.